Diabetes, antidiabetic medications, and pancreatic cancer risk: an analysis from the International Pancreatic Cancer Case-Control Consortium - Bosetti, C; Rosato, V; Li, D; Silverman, D; Petersen, G M; Bracci, P M; Neale, R E; Muscat, J; Anderson, K; Gallinger, S; Olson, S H; Miller, A B; et al. (Annals of oncology, 2014)
BACKGROUND: Type 2 diabetes mellitus has been associated with an excess risk of pancreatic cancer, but the magnitude of the risk and the time-risk relationship are unclear, and there is limited information on the role of antidiabetic medications. PATIENTS AND METHODS: We analyzed individual-level data from 15 case-control studies within the Pancreatic Cancer Case-Control Consortium, including 8305 cases and 13 987 controls. Pooled odds ratios (ORs) were estimated from multiple logistic regression models, adjusted for relevant covariates. RESULTS: Overall, 1155 (15%) cases and 1087 (8%) controls reported a diagnosis of diabetes 2 or more years before cancer diagnosis (or interview, for controls), corresponding to an OR of 1.90 (95% confidence interval, CI, 1.72-2.09). Consistent risk estimates were observed across strata of selected covariates, including body mass index and tobacco smoking. Pancreatic cancer risk decreased with duration of diabetes, but a significant excess risk was still evident 20 or more years after diabetes diagnosis (OR 1.30, 95% CI 1.03-1.63). Among diabetics, long duration of oral antidiabetic use was associated with a decreased pancreatic cancer risk (OR 0.31, 95% CI 0.14-0.69, for ≥15 years). Conversely, insulin use was associated with a pancreatic cancer risk in the short term (OR 5.60, 95% CI 3.75-8.35, for <5 years), but not for longer duration of use (OR 0.95, 95% CI 0.53-1.70, for ≥15 years). CONCLUSION: This study provides the most definitive quantification to date of an excess risk of pancreatic cancer among diabetics. It also shows that a 30% excess risk persists for more than two decades after diabetes diagnosis, thus supporting a causal role of diabetes in pancreatic cancer. Oral antidiabetics may decrease the risk of pancreatic cancer, whereas insulin showed an inconsistent duration-risk relationship.
Keywords: Logistic Models; Insulin; diabetes; Male; pancreatic cancer; inzulin; Risk Factors; pooled analysis; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Diabetes Mellitus, Type 2; case–control study; oral antidiabetics; diabetes mellitus 2. typu; Smoking; Pancreatic Neoplasms; logistické modely; senioři nad 80 let; hypoglykemika; lidé; ženské pohlaví; studie případů a kontrol; insulin; Humans; nádory slinivky břišní; rizikové faktory; Aged, 80 and over; Hypoglycemic Agents; Female; lidé středního věku; kouření; Middle Aged